Depression in Sylvia Plath and Abu Alqasem Al Shabbi's Selected Poems: A Comparative Study - Ahmed Taher Abdu Nagi (Taez University, 2023)
Depression is a universal phenomenon that can haunt men as well as women regardless of any social, cultural or literary background. Sylvia Plath and Abu Alqasem Al Shabbi are two poets whose poetry reflects the prevailing concept of depression due to some inner as well as outer causes. This study is significant since it investigates depression of two poets from different cultures despite the short span of their lives. It presents Al Shabbi as a paralleling poetic figure to Plath. The present study aims at investigating these causes of depression and to figure out similarities and differences between Plath and Al Shabbi's depression in the selected poems 'Daddy, Lady Lazarus, Tears and The Nameless Depression'. The presents study has used the descriptive, analytical and comparative approach. In spite of the fact that Plath and Al Shabbi did not live at the same time and culture, depression is the uniting factor between them. This study concludes that depression in the case of Plath is due to the patriarchy of men over women in America whether a father, a husband or any male-figure whereas depression in the case of Al Shabbi is due the patriarchy of the same literary gender in Tunisia.